Maintenance performance improvement analysis using Fuzzy Delphi method: A case of an international lube blending plant in Malaysia - Ghazali, Z. (2019)
Purpose: The purpose of this paper is to analyze issues pertaining to maintenance performance and to develop a framework that addresses challenges of maintenance management of an international lube blending plant in Malaysia. This study capitalizes on the contribution of selected maintenance department stakeholders from within the plant to develop âtailor-madeâ intervention strategies for maintenance performance improvement. Design/methodology/approach: The study employed two focus group workshops to ascertain issues facing the maintenance department and identify intervention strategies. The final phase of the study employed fuzzy Delphi method (FDM) to prioritize and rank the intervention strategies for performance improvement. Findings: The first focus group workshop identified 106 issues which could be classified under aspects of spare parts (n=8), equipment (n=14), communication (n=12), non-technical resource (n=8), health, safety and environment (n=4), technical skills and recruitment (n=27), and handling and procedures (n=33). Based on these findings, the second focus group revealed 28 significant performance initiatives to improve the issues identified for maintenance performance improvement. Through the FDM, 18 performance initiatives were ranked and prioritized. Performance improvement through leadership category leads the overall initiatives followed by equipment maintenance management, talent management, work environment and vendor management. Research limitations/implications: Interesting implications for maintenance management theory would be realized if future research were able to demonstrate that certain aspects or dimensions were related to high performing plant maintenance, and not with low performing ones. Apparently, the present study is not able to provide this clue because it is merely a case study of a single company. Practical implications: As ILBP attempts to implement maintenance performance improvement, it is pertinent for the management to understand the relevant performance issues and concerns. The appropriate enablers have been identified and must be initiated to chart the strategic role of their maintenance organization. Social implications: This study contributes toward further understanding of the maintenance performance management. It has demonstrated the need of organizations to make infrastructural investments such as quality leadership, employee training and empowerment, to name a few, to strategically enhance their maintenance capabilities. Originality/value: This study uses the FDM for the decision-making process of improving plant maintenance performance. It adds value to the body of knowledge of plant operation management. Â© 2019, Emerald Publishing Limited.